2008
DOI: 10.4103/0973-1229.33006
|View full text |Cite
|
Sign up to set email alerts
|

Medical Ghost-Writing

Abstract: Any assistance an author receives with writing a scientific article that is not acknowledged in the article is described as ghost-writing. Articles ghost-written by medical writers engaged by pharmaceutical companies who have a vested interest in the content have caused concern after scandals revealed misleading content in some articles. A key criterion of authorship in medical journals is final approval of the article submitted for publication. Authors are responsible for the content of their articles and for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Wooley et al, 2006). 4 As a matter of fact, Langdon-Neuner (2008) reckons that ACKs are the solution to the problem of ghostwriting. Her argument is that authors are not only responsible for the content of their papers but also for acknowledging any assistance they received while conducting their research.…”
Section: Introductionmentioning
confidence: 99%
“…Wooley et al, 2006). 4 As a matter of fact, Langdon-Neuner (2008) reckons that ACKs are the solution to the problem of ghostwriting. Her argument is that authors are not only responsible for the content of their papers but also for acknowledging any assistance they received while conducting their research.…”
Section: Introductionmentioning
confidence: 99%
“…Ghost authorship exists if individuals writing the trial protocol, performing the statistical analysis or writing the manuscript are neither listed as authors nor acknowledged in the manuscript. In a study comparing clinical trial protocols provided by an ethics committee with corresponding publications reporting the results in medical journals, ghost authorship for 33 of 44 trials was identified [75]. In what follows, clinicians—owing their professional career to research grants from a manufacturer and/or to high-impact publications written by ghostwriters—are promoting new treatments or products supported by the industry as important innovations [67].…”
Section: Proposal To Link Different Typologies Of Corruptionmentioning
confidence: 99%
“…If their contribution does not qualify them to be authors, they should be adequately acknowledged in the Acknowledgement or the Contributors sections (11,12). …”
Section: The Authorship Dilemmamentioning
confidence: 99%